Comparative evaluation of laser-microtextured implant versus machined collar implant for soft and hard tissue attachment: A clinical and radiological study - Saroj Kumar Rath; Manab Kosala; Ankit Gupta (Wolters Kluwer Medknow Publications, 2017)
Background: Various mechanical modifications in the collar region of endosseous implants is a challenge for better performance and osseointegration. Here is a comparative evaluation being carried out to find out the effect of the machined collar (MC) and Laser-Lok (LL)-modified titanium implants on the success of implants being commonly advocated in partially edentulous among serving personnel and their families. Materials and Methods: Twenty-four patients with appropriate inclusion and exclusion criteria were selected for placement of Biohorizons MC and LL implants in 12 cases each. Aseptic surgical procedure was followed for implant surgery, and clinical parameters such as clinical attachment loss, pocket depth (PD), bleeding on probing, and plaque index (PI), mobility parameters estimated by Periotest value, and radiographic assessment of crestal bone loss (CBL) at interval of 6 months and 1 year were recorded and compared by statistical analysis. Results: Intragroup comparison at 6 and 12 months period for all the parameters were nonsignificant except CBL in Group A (CBL-MC) with 12 cases shows a mean of 0.917 and 1.500, respectively, standard deviation difference = 0.477 (significant) with P < 0.05. Similar significant difference in CBL was observed with superior result in LL implants. Conclusion: The presence of LASER textured with microgrooves on the collar of the implants did not increase the PI and sulcular bleeding index. The probing PD was much less as observed in the group of LASER-treated implants in comparison with that of MC group. LL implant had an edge over MC proving success of the laser treatment on collars of implants.